THE EFFECT OF HEALTH PROTOCOL, WORK FROM HOME, INFORMATION TECHNOLOGY SYSTEM AND WORK LIFE BALANCE ON EMPLOYEES’ PERFORMANCE OF BANK INDONESIA REPRESENTATIVE OFFICE IN EAST JAVA PROVINCE - Adrian Denar Wahyu Nugraha; Slamet Riyadi; Sunu Priyawan (UNUSA Press, 2022)
This study is to prove and analyze the effect of health protocols, work from home and information technology systems on the work life balance and employee performance at the Bank Indonesia Representative Office in East Java Province. The method used in this study is quantitative and explanatory in nature, namely a study that highlights between variables and tests a hypothesis that has been formulated in the form of causality (influence) that examines the effect (determinant) of one or more independent variables on one or more dependent variables.